Absence of coronary angioscopy-derived in-stent thrombi is associated with major bleeding events in acute myocardial infarction. (February 2021) - Ohgaku, Akihito; Fukamachi, Daisuke; Takahashi, Kurara; Tamiya, Ran; Migita, Shohei; Mizobuchi, Saki; Miyagawa, Masatsugu; Koyama, Yutaka; Fujito, Hidesato; Arai, Riku; Ebuchi, Yasunari; Migita, Suguru; et al.
Abstract: Background and aims: The optimal duration of dual antiplatelet therapy for acute myocardial infarction is controversial because the bleeding risk outweighs the thromboembolic risk. We hypothesized that an in-stent thrombus (IS-thrombus) detected by coronary angioscopy (CAS) after stent implantation would be associated with high bleeding risk. Methods: This study included 208 patients who underwent CAS at 2 weeks after stent implantation for an acute myocardial infarction. The study was approved by the ethics committee at the Nihon University Itabashi Hospital (reference number RK-200714-10). Results: In 84 patients, in whom no IS-thrombus was identified in the culprit vessel using CAS, the major bleeding event rate was significantly higher than that in patients with IS-thrombi (n = 124). However, no difference was detected in major adverse cardiovascular events (MACE; stroke, hospitalization for a non-fatal myocardial infarction/unstable angina, target lesion revascularization, and cardiovascular death). After adjustments by the propensity score based on patient characteristics, the absence of IS-thrombi remained an independent predictor of major bleeding events (hazard ratio 4.73, 95% confidence interval 2.04–11.00, p  < 0.001). Conclusions: The absence of CAS-detected IS-thrombi in the subacute phase was independently associated with future major bleeding events, but not with MACE. These findings may help optimize the duration of dual antiplatelet therapy. Graphical abstract: Image 1 Highlights: Absence of in-stent thrombi detected by coronary angioscopy is linked to future bleeding. Absence of in-stent thrombi is not associated with major adverse cardiovascular events. Presence vs . absence of thrombi may suggest the duration of the dual antiplatelet therapy.